2009
DOI: 10.1143/jpsj.78.044802
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Energy Controls the Heme-Fe Valence in Aqueous Myoglobins

Abstract: We use resonant X-ray emission spectroscopy and model calculations to quantify the ligand: heme-Fe energy structure of aqueous myoglobins. For reduced (Fe 2þ ) and oxidized (Fe 3þ ) states, the removal or addition of an electron primarily involves charge changes on the ligand-site, and not the Fe-site. The results indicate a finite positive/negative charge-transfer energy Á between the heme-Fe 3d and ligand valence electronic states for Fe 2þ /Fe 3þ . Thus, the energy difference between the ligand and Fe 3d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…The Mn-3d electrons are delocalized and strongly hybridized with the O-2p orbital in the wide energy range when the CT energy is negative. These mechanism were reported in previous paper [10].…”
Section: Resultssupporting
confidence: 87%
“…The Mn-3d electrons are delocalized and strongly hybridized with the O-2p orbital in the wide energy range when the CT energy is negative. These mechanism were reported in previous paper [10].…”
Section: Resultssupporting
confidence: 87%
“…We also note that a still larger ðpdÞ (¼ À5:44= ffiffi ffi 3 p eV ¼ À3:18 eV) is assumed in the cluster model analysis of the Fe 2p resonant X-ray emission of cyanomet myoglobin. 30) …”
Section: Energy Levels Of Divalent Fe Cyanidesmentioning
confidence: 99%
“…A problem is radiation damage of biological specimens, and as a beginning, experiments were made on rather stable molecules such as myoglobin, at 77 K. Shifting the sample along the beam allows one to investigate undamaged molecules. The high -and low -spin confi guration of the center iron of the heme site of myoglobin could be clearly distinguished [154] . Due to the resonant optical behavior at the core shell absorption edges of elements, it has been shown that Cherenkov radiation can be generated in comparably narrow spectral segments in the soft X -ray region [155] .…”
Section: Selected X -Ray Surface/interface Analysis Methodsmentioning
confidence: 98%